Investigating the types and mechanisms of Mycobacterium tuberculosis resistance: why Indonesia continues to experience high case rates compared to other nations - Siswanto, Melinda; Kusnadi, Angelica Laura; Armevia, Nandya Zahra; Agustin, Regita (Current Research on Biosciences and Biotechnology, 2025)
Tuberculosis (TB) cases in Indonesia have been a major issue in public health. Although antimicrobial therapies such as Isoniazid and Rifampicin are available, Indonesia still struggle to control its spread and yet to eradicate the infection. This is due to the resistance developed by Mycobacterium tuberculosis, the main cause of TB, causing an increasing number of Extensively Drug-Resistant Tuberculosis (XDR-TB). This problem exacerbates by the inadequacy of healthcare infrastructure to effectively detect and treat TB. Hence, this study is established to address the challenges and strategies for controlling TB and XDR-TB in Indonesia. The analysis involves epidemiological studies, genetic research, and public health policy reviews to identify the factors contributing to TB drug resistance and to propose targeted interventions. The findings reveal that high drug resistance and inadequate healthcare infrastructure are major barriers. Evidence-based interventions and enhanced diagnostic capacity are crucial for controlling TB in Indonesia. Socioeconomic factors like poverty and limited access to healthcare services also influence the spread of TB in Indonesia. Improving the healthcare system and addressing socioeconomic issues can help reduce TB and XDR-TB rates.